Hubungan Antara Tingkat Pengetahuan dan Perilaku Tentang Katarak Diabetika Penderita Diabetes Mellitus dengan Kejadian Katarak di Puskesmas Gunung Pati Semarang - Dhaniswara, Andhika Adristia; Saubig, Arnila Novitasari; Pramono, Dodik; Nugraheni, Arwinda (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Cataract is a degenerative disease that causes second highest visual impairment and the highest cause of blindness in the world which is multifactorial. The behavior and knowledge of people with diabetes mellitus in controlling their disease is important considering that diabetes mellitus is one of the significant factors causing cataracts especially if not treated properly.Methods: This research is an observational analytical with cross-sectional approach. The research data was obtained using consecutive sampling from patients with diabetes mellitus who come to the Gunungpati public health center. Research subjects used in this research were 53 patients who fulfill the inclusion and exclusion criteria, the data then analyzed using Chi-square test.Result: There is a significant relationship between the patient’s level of knowledge (p=0,004;OR=5,56;CI=1,67-17,54) and behavior (p=0,04;OR=3,19;CI=1,04-9,80) on the incidence of cataracts.Conclusion : There is a significant relationship between level of knowledge and behavior of people with diabetes mellitus regarding diabetic cataracts on the incidence of cataracts.